The Role of the World Food and Agriculture Organization on Food Security in Indonesia - Gusmita Indah P (Institute of Computer Science (IOCS), 2020)
Writing is about how the role of the Food and Agriculture Organization of the food security in Indonesia. Food security to be studied in this thesis, in which Indonesia is a rich agricultural country in natural resources and the majority of the population are farmers impossible feels when food security is threatened. Food security includes not only understanding the availability of adequate food, but also the ability to access the food and not the food dependence on any party. When you view the current state of Indonesian food, the amount of the transfer of agricultural land that makes the reduced agricultural products in Indonesia. So naturally when Indonesia experienced food shortages that have to import to meet food needs. FAO or the Food and Agriculture Organization is a specialized agency of the United Nations (UN) which aims to meet the food needs and improve the food security of its people. With the organization of course there will be changes madein ketahann food. Many things concerning the role of these organizations in the context of such political influence government policy in terms of food